Effects of telerehabilitation and YouTube platform-based exercise videos in patients with axial spondyloarthritis: a randomized controlled study - Yentur, Songul Baglan; Boyrazli, Irem Sila; Elbasti, Muhammed Sahin; Koca, Suleyman Serdar (Springer London Ltd, 2025)
Introduction: Exercise is an important part of the treatment for axial spondyloarthritis (axSpA). Telerehabilitation (TR) may be a good alternative for the patient group who cannot access face-to-face exercise. In addition, with the developing technology, social media platforms are used in rehabilitation. The aim of this study was to compare the effects of TR and YouTube (R)-based exercises on disease activity, function, mobility, quality of life, and posture in patients with AS. Methods: The study included 44 patients with axSpA. The patients were randomly divided into two groups. The first group practised TR via video conferencing, while the other group was recommended high-quality videos on YouTube (R) according to the Global Quality Scoring for 8 weeks. Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Function Index (BASFI), Bath Ankylosing Spondylitis Metrology Index (BASMI), Ankylosing Spondylitis Quality of Life, and PostureScreen application were used to evaluate disease activity, function, mobility, quality of life, and posture, respectively. Results: The study was completed with 39 axSpA patients. There was no significant difference between TR and YouTube (R) groups in evaluation parameters (p > 0.05). A significant difference was obtained in head tilt forward (p = 0.03), but no significant difference was obtained in other parameters (p > 0.05) between groups after treatment. In addition, significant differences were concluded in disease activity (p = 0.003), function (p = 0.029), and mobility (p = 0.001) at comparison of before and after treatment in TR group, while no significant difference was found in the YouTube (R)-based exercise group (p > 0.05). A significant difference was obtained in the TR group in head tilt forward (p = 0.009) and shoulder angle right side (p = 0.028) in the lateral posture analysis before and after treatment. Conclusion: It was concluded that TR was effective on disease activity, mobility, and function in patients with axSpA. TR and YouTube (R) exercises can be safely applied in patients with axSpA. Studies comparing face-to-face and supervised exercises with TR applications are needed.
Keywords: Ankylosing spondylitis; Exercise; Telerehabilitation; YouTube (R)